HASIL BELAJAR PKN DENGAN MENGGUNAKAN MODEL SOCIAL PROBLEM SOLVING DI KELAS V SDN 01 KECAMATAN GUGUAK - ramadhanti, fitra; reinita, reinita; mahyuddin, ritawati (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
ABSTRACT The purpose of this research was to describe an increase in student learning outcomes in Civics learning with the Social Problem Solving Model in class V 01 SDN VII Koto Talago Guguak Subdistrict. This type of research is Class Action Research using qualitative and quantitative approaches with planning, implementation, observation, and reflection. Research data from observations, test results and non-tests. Conducted in Semester I Academic Year 2018/2019. The research subjects were teachers as observers, researchers as practitioners, and class V students as many as 20 people, namely 7 men and 13 female students. The results of the first cycle of research on lesson plans averaged 67.85% (sufficient), increasing in the second cycle to 89.3 % (well). The implementation of the first cycle on the aspect of the teacher averaged 80.55% (good), increased in the second cycle to 97.22% (very good). The implementation of the first cycle on the aspects of students on average 66.66% (sufficient), increased in the second cycle to 94.44% ( very good). Student learning outcomes in the first cycle averaged 74.30 (enough), increased in the second cycle to 89.17 (good). Can be concluded Model Social Problem Solving shows an increase in student learning outcomes in Civics learning in class V Public Elementary School 01 VII Koto Talago District Guguak. Keywords: Social Problem Solving model, PKn Learning Outcomes, Elementary Students